Academic Procrastination of Students at SMAN 6 Prabumulih in Terms of the Intensity of Smartphone Usage - Putri, Itsmi Annisa; Putri, Rani Mega; Alrefi, Alrefi (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to describe the level of academic procrastination of class XI students at SMAN 6 Prabumulih in terms of the intensity of smartphone usage. The method used in this research is descriptive quantitative. The data collection technique used was by distributing research instruments, namely questionnaires with a Likert scale model. The data obtained were then analyzed using categorization formulas and percentages (%). The population in this study were all 263 students of class XI at SMAN 6 Prabumulih with a sample selected by a simple random technique of 158 students based on the calculation of sampling using the slovin formula. The results of this study indicate that in general students have a medium level of academic procrastination when viewed from the intensity of their smartphone usage.